IMPLEMENTASI APLIKASI SIMBADA PADA PELATIHAN PENGELOLAAN ASET DAN INVENTARIS SEKOLAH DALAM PENINGKATAN KINERJA PEGAWAI ADMINISTRASI SMA NEGERI 22 SURABAYA - Damayanti, Eka; Anisa, Nur Aini; Megasari, Aisyah Darti (STIE PENA, 2023)
This study aims to determine the training of regional property management related to school assets and inventory based on SIMBADA application in improving the performance of administrative staff in infrastructure affairs at SMA Negeri 22 Surabaya. In this study using qualitative research methods. The data collection techniques used are interview, observation and documentation techniques. The results showed that the SIMBADA application training proved to be very effective in contributing and supporting the improvement of the quality of regional goods management to accelerate and facilitate the use of goods, and was able to support all employee activities, especially goods administrators or administrative staff in infrastructure facilities in carrying out administration of regional goods management as much as possible and much better.